Children Trust a Consensus Composed of Outgroup Members—But Do Not Retain That Trust. Issue 1 (19th September 2012) - Chen, Eva E.; Corriveau, Kathleen H.; Harris, Paul L.
<x xml:space="preserve">Abstract</x> Children prefer to learn from informants in consensus with one another. However, no research has examined whether this preference exists across cultures, and whether the race of the informants impacts that preference. In 2 studies, one hundred thirty‐six 4‐ to 7‐year‐old European American and Taiwanese children demonstrated a systematic preference for a consensus. Nevertheless, the initial strength and persistence of that preference depended on the racial composition of the consensus. Children's preference for consensus members belonging to the same race as themselves persisted even when only one consensus member remained to provide information. When the consensus consisted of different‐race informants, preference for the consensus was initially apparent but lost when only one member from the consensus remained with the dissenting informant.